1999
DOI: 10.1021/ma9805553
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Interfacial Tension and Dispersed Phase Morphology in Interfacially Modified Blends of LLDPE and PVC

Abstract: To study the phase size/interfacial tension relationship for LLDPE/PVC blends over a wide range, three modifiers of widely varying efficacy were chosen based on a cursory analysis of their acid−base interactions with the blend system. The modifiers used were poly(isoprene−4-vinylpyridine) (PIP−P4VP), poly(styrene−acrylic acid) (PS−PAA), and a hydroxyl-terminated polystyrene (PS−Si(CH3)2OH). The ternary blend systems were rigorously characterized by tracking both interfacial tension and dispersed phase morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…27 In that work a composition study revealed that no coalescence occurred in that system even for blends containing 25% dispersed PVC. This was considered to be due to the low interfacial tension between the matrix and the dispersed phase (3.5 mN/m).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…27 In that work a composition study revealed that no coalescence occurred in that system even for blends containing 25% dispersed PVC. This was considered to be due to the low interfacial tension between the matrix and the dispersed phase (3.5 mN/m).…”
Section: Introductionmentioning
confidence: 89%
“…Second, the reduction in the particle size of the compatibilized 1% dispersed phase system is due exclusively to the interfacial tension because coalescence can be considered to be negligible in that system. If it is assumed that the direct dependence of interfacial tension to particle diameter holds for concentrated systems, 23,27 then it should be possible to factor out the reduction in particle diameter due to coalescence suppression.…”
Section: Relative Role Of Interfacial Tension and Coalescencementioning
confidence: 99%
“…Thus, interfacially active copolymers are added [27][28][29][30][31][32][33][34][35][36][37][38] or formed in situ during processing by an interfacial reaction of added functionalized polymeric components [27,[38][39][40][41][42]. The aim of this interfacial compatibilization is to lower interfacial tension, to decrease the dispersed phase domain size, to hinder coalescence, to improve adhesion and to stabilize the morphology [38,[43][44][45][46]. Additionally, surfaces (and interfaces) of (solid) polymers can be modified by plasma treatments either to graft molecules onto the polymer [56][57][58] or to increase the surface energy and the hydrophilicity [50].…”
Section: Introductionmentioning
confidence: 99%
“…In the first reports issued from the study [1][2][3][4] attention was focussed on the use of diblock copolymers with a variety of functional groups, as modifiers of surfaces and of interfaces in systems based on the immiscible polymer combination of polyvinyl chloride (PVC) and linear, low-density polyethylene (LLDPE). In one part of the work 1,3 the copolymers were applied to rutile pigments in an attempt to modify the solids in a manner appropriate to the interac-tion characteristics of the component polymers and to evaluate their effectiveness as modifiers of the blends' mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In one part of the work 1,3 the copolymers were applied to rutile pigments in an attempt to modify the solids in a manner appropriate to the interac-tion characteristics of the component polymers and to evaluate their effectiveness as modifiers of the blends' mechanical properties. Elsewhere 2,4 the emphasis was on the morphology of interfaces in polyblends containing various of the copolymers, and on their effectiveness in modifying the interfacial tension of the PVC/LLDPE pair. Considerable emphasis has been and continues to be placed on quantitative measurements of specific (or acid-base) interactions as a means of rationalizing observations and of providing guidelines for the preferred modification strategy to be followed to targeted performance ends.…”
Section: Introductionmentioning
confidence: 99%